2014
DOI: 10.5194/acp-14-6195-2014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tropical land convection on the water vapour budget in the tropical tropopause layer

Abstract: Abstract. The tropical deep overshooting convection is known to be most intense above continental areas such as South America, Africa, and the maritime continent. However, its impact on the tropical tropopause layer (TTL) at global scale remains debated. In our analysis, we use the 8-year Microwave Limb Sounder (MLS) water vapour (H 2 O), cloud ice-water content (IWC), and temperature data sets from 2005 to date, to highlight the interplays between these parameters and their role in the water vapour variabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 68 publications
1
30
0
Order By: Relevance
“…Also diurnal effects (e.g. Carminati et al, 2014) can play a role if there is a systematic time difference between the data sets (e.g. Damadeo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also diurnal effects (e.g. Carminati et al, 2014) can play a role if there is a systematic time difference between the data sets (e.g. Damadeo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regional effects of overshooting have been detected in various tropospheric tracers, such as N 2 O, CH 4 and CO (Ricaud et al, 2007(Ricaud et al, , 2009 . Carminati et al (2014) used MLS daytime and night-time observations to investigate the diurnal cycle of water vapour, cloud ice-water and temperature.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In contrast to that, Randel et al (2015) found that enhanced tropospheric convection within Asian and North American monsoons leads to reduced stratospheric water vapour. While upscaling the overshooting events and quantifying their net effect on water vapour remains a difficult task, various space-borne observations suggest that the most vigorous convection, capable of direct transport of material into the lower stratosphere, is mostly restricted to the tropical land regions (Liu and Zipser, 2005;Ricaud et al, 2009;Iwasaki et al, 2010;Bergman et al, 2012;Khaykin et al, 2013a;Carminati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although seasonal and annual variations of H 2 O have been extensively studied, few studies were devoted to the geographical and temporal variability of its diurnal cycle in the TTL. In Carminati et al (2014), the impact of the continental tropical convection on the H 2 O variability was debated by considering the 8-year Microwave Limb Sounder (MLS) H 2 O, cloud ice water content and temperature data sets from 2005 to 2014. The interplays between these parameters and their role in the water vapour variability in the TTL were highlighted separately in the northern and southern tropics.…”
Section: Introductionmentioning
confidence: 99%
“…The interplays between these parameters and their role in the water vapour variability in the TTL were highlighted separately in the northern and southern tropics. The analysis from Carminati et al (2014) adopted the Liu and Zipser (2009) philosophy to discuss the difference between daytime and night-time data sets, with the aim of better apprehending the role of continental convection in hydrating and dehydrating processes in the TTL.…”
Section: Introductionmentioning
confidence: 99%